Therapeutic options at the Neonatal Pathology Ward - Monika Joanna Stecko; Agata Wawrykow; Katarzyna Korabiusz-Lewandowska; Agnieszka Kordek (Kazimierz Wielki University, 2020)
According to the World Health Organization, premature baby is a newborn baby that was born between 22nd and 37th week of pregnancy. The premature babies, due to immaturity of all systems, require special care from the whole medical personnel and holistic approach. The role of a physiotherapist at the Neonatal Pathology Ward is a very important aspect and care of a little patient should be adjusted individually. The most important assumptions of the methods in the care of premature babies at the intensive care unit include normalization of muscle tension, change of abnormal posture and motor patterns, as well as normal sensory experiences. Techniques and supports adjusted to physical and personality capabilities of a child are applied during therapy [1,2]. The Neonatal Pathology Ward is also a place for a clinical speech therapist who has a very important task in the care of a premature baby. A speech therapist who deals with therapy of a premature baby, checks anatomical conditions of the oral cavity, that is, tongue mobility, length of a frenulum, structure of the palate, and then develops a model of support individual for every patient [3]. Interdisciplinary work of the members of a medical team is necessary to provide modern and professional care for the patients.